(untitled) (Current Problems in Rail Vehicles, 2025)
The paper describes the initial operational concept of electric multiple units with traction batteries in the Czech Republic following their introduction into trial operation as well as preparations for the deployment of additional units from the already ordered series for the Moravian-Silesian Region. Furthermore, it outlines the changes and operational measures implemented at the maintenance site to ensure the safety and reliability of battery-equipped vehicles. The next part of the paper focuses on the maintenance requirements of the running gear of electric units, which are now also operated on regional lines with very small curve radii. To mitigate the effect of track geometry on the wheelsets, various measures are or will be implemented by vehicle maintenance and by the infrastructure manager.